The Effect of Some Immunological Markers (IgM, IgG, CCP, IL1) Associated with RA in a Sample of Iraqi Patients: Pengaruh Beberapa Penanda Imunologi (IgM, IgG, CCP, IL1) yang Berhubungan dengan RA pada Sampel Pasien Irak - Ahmed, Atheer Shehab; Al-Ezee, Ali Shakir; Sahm, Sara Fawzi (Indonesian Journal on Health Science and Medicine, 2024)
This work was performed on Iraqi patients with rheumatoid arthritis. It collected blood samples from 60 patients with RA whose ages range between 21-70 years. The study included more females than males, as the former was 55 by 91.7%, while the latter was 5 at 8.3%. To compare, 28 other blood samples were drawn from healthy control participants who range from 21-60 years, and the males was 5, 17.9%. The females were 23 by 82.1%, as the highest was in the ages 41-60 years and 51.7 and the age group (≤20) years (3.3%) was lowest as the disease among non-smokers(90.0%) is the largest in comparison to the rate among smokers (10.0%) with significant differences (P<0.001). The disease among married couples (80.0%) was statistically different (P<0.01) as the largest in reference to the unmarried and (20.0%). A significant rise (P<0.001) in Intreleukin- 1 alpha in patients 2.87 units/ml appeared while in healthy people 1.36 units/ml, and a significant rise "(P<0.001) in cyclic citrullinated peptides antibody in the blood of patients relative to the healthy". Here, the protein in the patients' blood was 406.62 mg/L and the 66.07 mg/L in the healthy. A high significant rise (P<0.001) was seen in immunoglobulin IgG in patients rising to 3.39 (ug/ml) and the healthy 0.72 (ug/ml). A significant rise happened (P<0.001) in the immunoglobulin IgM in patients reaching 8.75 (ug/ml).) compared to the healthy at 5.32 (ug/ml). Highlights: Demographics: RA affects mostly females (91.7%), non-smokers (90%), and married (80%). Biomarkers: Significant increases in IL-1α, CCP antibody, IgG, and IgM in RA. Controls: Healthy controls show lower biomarker levels compared to RA patients. Keywords: Marker, IgM, IgG, CCP, IL1.